2022
DOI: 10.3390/ijerph20010408
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Risk Factors for Conversion from Laparoscopic to Open Cholecystectomy: A Systematic Review and Meta-Analysis

Abstract: Laparoscopic cholecystectomy is a standard treatment for patients with gallstones in the gallbladder. However, multiple risk factors affect the probability of conversion from laparoscopic cholecystectomy to open surgery. A greater understanding of the preoperative factors related to conversion is crucial to improve patient safety. In the present systematic review, we summarized the current knowledge about the main factors associated with conversion. Next, we carried out several meta-analyses to evaluate the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The study included challenging cases and involved bile duct exploration. In another study, it was reported to range from 1 to 23.3%, underscoring the significance of training and sub-specialization (31). Emphasizing a high case volume and employing strategies such as subtotal cholecystectomy can help reduce CR.…”
Section: Discussionmentioning
confidence: 98%
“…The study included challenging cases and involved bile duct exploration. In another study, it was reported to range from 1 to 23.3%, underscoring the significance of training and sub-specialization (31). Emphasizing a high case volume and employing strategies such as subtotal cholecystectomy can help reduce CR.…”
Section: Discussionmentioning
confidence: 98%
“…[12] Furthermore, the urgency of the patient's clinical condition may have factored into the surgeon's decision, leading them to conclude that an open surgical approach was the most prudent and efficacious course of action. The distinct presentation and anatomical variances of each patient should be considered while deciding between an open and a laparoscopic cholecystectomy [11,13] (Supplementary Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it remains necessary to identify patients at risk of having required unplanned conversion to open cholecystectomy. In conjunction with the pro-inflammatory state of obesity, the current analysis further identified increasing age and male sex to be associated with a higher likelihood of CTO [ 33 ]. While reasons for this are likely multifaceted, inflammation secondary to both age and male sex is a proposed factor [ 33 ].…”
Section: Discussionmentioning
confidence: 99%